Identity and Conflict in Tuscany - Honess, Claire; Ross, Silvia (Studi e saggi, 2015)
This volume represents a targeted exploration of the theme of identity and conflict in the context of Tuscan Studies, an exploration which is enriched by the diverse disciplinary perspectives encompassed (history, literature, linguistics). The essays, which span the period from the nineteenth century to the present, examine conflict in terms of war but also as a form of struggle between different demographic groups or conflict based on gender and identity politics. This collection thus signals an original mode of analysis of the region, while drawing on the proven interest, both scholarly and popular, in its history, literature, language, art and society.